2013
DOI: 10.35790/ebm.1.1.2013.1175
|View full text |Cite
|
Sign up to set email alerts
|

GAMBARAN KADAR ASAM URAT PADA MAHASISWA ANGKATAN 2011 FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI DENGAN INDEKS MASSA TUBUH ≥ 23 kg/m2

Abstract: The increase of blood uric acid beyond the normal limit (hyperuricemia) results an increase of risks and mortalities in several diseases. Nowadays, the prevalence of hyperuricemia appears to be increasing in develop countries. Hyperuricemia is a disease correlated with obesity in children and adults. This study aimed to determine the blood uric acid among the students of Faculty of Medicine, Sam Ratulangi University 2011 with body mass index (BMI) ≥23 kg/m2. This was a descriptive study, using a purposive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
1
0
4
Order By: Relevance
“…This may be due to genetic factors that contribute to elevated uric acid levels and reduced physical activity (Rau, Ongkowijaya, & Kawengian, 2015). Another study found their high levels of uric acid in the respondents overweight and obesity with the possible result of a decrease in renal excretion of uric acid due to insulin resistance and hyperinsulinemia occurring in the state of overweight and obesity (Karimba, Kaligis, and Purwanto, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to genetic factors that contribute to elevated uric acid levels and reduced physical activity (Rau, Ongkowijaya, & Kawengian, 2015). Another study found their high levels of uric acid in the respondents overweight and obesity with the possible result of a decrease in renal excretion of uric acid due to insulin resistance and hyperinsulinemia occurring in the state of overweight and obesity (Karimba, Kaligis, and Purwanto, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Sehingga pada keadaan hiperinsulinemia pada pra diabetes terjadi peningkatan reabsorbsi yang akan menyebabkan hiperurisemia. 8,9 Konsumsi makanan sehari-hari dapat mempengaruhi kadar asam urat. Mengonsumsi makanan-makanan seafood dan daging sangat berpengaruh terjadinya gout.…”
Section: Uji Statistikunclassified
“…Sehingga pada keadaan hiperinsulinemia pada pra diabetes terjadi peningkatan reabsorbsi yang akan menyebabkan hiperurisemia. 8,9 Obesitas dapat didefinisikan sebagai kelebihan lemak tubuh. Penanda kandungan lemak tubuh yang digunakan adalah indeks masa tubuh (IMT), yang dapat dihitung sebagai Berat badan (kg)/Tinggi badan (m 2 ).…”
unclassified
“…4 Untuk prevalensi hiperurisemia di daerah Minahasa Sulawesi Utara berdasarkan penelitian yang dilakukan oleh Rotty yang memiliki prevalensi 34,30% pada laki-laki dan 23,31% pada perempuan. 5 Peningkatan kadar asam urat dalam darah (hiperurisemia) disebabkan oleh dua keadaan yang mengganggu keseimbangan kadar purin dalam tubuh manusia, yaitu peningkatan produksi purin dan penurunan ekskresi asam urat. Peningkatan produksi purin dapat disebabkan oleh karena konsumsi makanan tinggi purin sedangkan penurunan eksresi asam urat dapat terjadi akibat gangguan fungsi ginjal.…”
unclassified